1981
DOI: 10.3758/bf03198841
|View full text |Cite
|
Sign up to set email alerts
|

Stability of individual loudness functions obtained by magnitude estimation and production

Abstract: A correlational analysis of individual magnitude estimation and production exponents at the same frequency was performed, as well as an analysis of individual exponents produced in different sessions by the same procedure across frequency (250, 1,000, and 3,000 Hz). Taken together, results show, first, that individual exponent differences do not decrease by counterbalancing magnitude estimation with magnitude production, and, second, that individual exponent differences remain stable over time despite changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The exponent of loudness as a function of sound pressure is typically steeper for magnitude production than it is for magnitude estimation ( Reynolds and Stevens, 1960 ), i.e., a difference of less than 10 dB is required to double loudness. Stevens and co-workers found exponents of 0.7, corresponding to 9 dB being required to double loudness, in magnitude-production tasks ( Stevens and Guirao, 1962 ; Stevens and Greenbaum, 1966 ; Figure 5 ); Hellman (1981) reported an exponent of 0.81 (7 dB to double loudness) for a 1-kHz pure tone. Teghtsoonian and Teghtsoonian (1978) found that the exponent depended on the range of magnitudes that is presented.…”
Section: Discussionmentioning
confidence: 99%
“…The exponent of loudness as a function of sound pressure is typically steeper for magnitude production than it is for magnitude estimation ( Reynolds and Stevens, 1960 ), i.e., a difference of less than 10 dB is required to double loudness. Stevens and co-workers found exponents of 0.7, corresponding to 9 dB being required to double loudness, in magnitude-production tasks ( Stevens and Guirao, 1962 ; Stevens and Greenbaum, 1966 ; Figure 5 ); Hellman (1981) reported an exponent of 0.81 (7 dB to double loudness) for a 1-kHz pure tone. Teghtsoonian and Teghtsoonian (1978) found that the exponent depended on the range of magnitudes that is presented.…”
Section: Discussionmentioning
confidence: 99%